PENGARUH MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) BERBANTUAN MEDIA QUIZWHIZZER TERHADAP HASIL BELAJAR BAHASA INDONESIA PESERTA DIDIK DI SEKOLAH DASAR - Puspitasari, Andini; Mega Diana, Siska; Nuraini, Siti; Destini, Frida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this study was the low learning outcomes of Indonesian language students in elementary school. This study aimed to determine the effect of the Cooperative Integrated Reading and Composition (CIRC) model assisted by Quizwhizzer media on students' Indonesian language learning outcomes in elementary school. The research method used was a quasi-experimental design with a nonequivalent control group design. The research population consisted of 44 fourth-grade students of SD Negeri 8 Metro Utara. The sampling technique used was saturated sampling, so the entire population was used as the research sample. Data were collected through tests in the form of pretests and posttests, as well as observations. Data were analyzed using a simple linear regression test and a t-test. The results showed that the simple linear regression test obtained a significance value of less than 0.05, indicating that the Cooperative Integrated Reading and Composition (CIRC) model assisted by Quizwhizzer media had an effect on students' Indonesian language learning outcomes. The results of the t-test also showed a significance value of less than 0.05, indicating a significant difference in learning outcomes between the experimental class that used the Cooperative Integrated Reading and Composition (CIRC) model assisted by Quizwhizzer media and the control class that used the Problem Based Learning (PBL) model.